Draft Annual Plan 1979-80 (In 4 Volumes) Vol. II Haryana State - Planning Commission (Planning Commission, 1979)
Cumulative achievement of foodgrain production for the period 1974-78 is 95.4% of the targets, which is though on the lower side but very close to the target. Extreme drought conditions prevailed during Kharif 1974-75, the first year of the fifth Plan, which had dwindled the achievement of production to 50% of the target. This had also affected the low Rabi sowing upto the extent during Kharif 1977-78 which damaged the crops and resulted in the low production of Kharif foodgrains upto the level of 91.2% of the target. However this was compensated by taking timely action in Rabi sowing which resulted in the increased production of 105.1% of the target.
Planning Department, Government of Haryana